Multi-source Evaluation of Resident Physicians - Susan Michelle Nikels; Suzanne Brandenburg (Association of American Medical Colleges, 2012)
Abstract This module includes multisource assessment tools designed to be used by nonphysician coworkers as they evaluate resident physicians. At the University of Colorado Internal Medicine Residency Program, the authors were not obtaining useful information regarding resident performance and feedback from the continuity clinic multisource evaluations. Based on the results of a survey conducted in these continuity clinic sites, the authors developed a new multisource feedback assessment tool asking staff members to evaluate residents on professionalism, communication skills, and medical knowledge (nurses only). The module includes an instruction guide to describe the process of obtaining multisource evaluations. Implementation suggestions, including tips and pitfalls, are included. Also included is the multisource assessment tool used by the authors in clinical setting involving nurses. This tool includes questions about resident professionalism, communication skills, and medical knowledge. It should be noted that this multisource assessment tool is used by its authors in their continuity clinic setting, where the residents work mostly with medical assistants rather than nurses is included. This assessment tool includes questions about resident professionalism, communication skills, and response to feedback. Both of these assessment tools can be adapted to fit a variety of clinical sites including both inpatient and outpatient settings. The first year the new tool was implemented, we saw improvement in feedback on resident professionalism and communication skills but still limited responses to questions about medical knowledge due to lack of resident interaction with the nurses in clinic. The tool was then modified by removing the questions about medical knowledge and incorporating questions about resident learning and improving through feedback.